Swiss Graphic Design Histories – Visual Arguments - Bischler, Sandra; Klein, Sarah; Niedermann, Jonas; Renner, Michael (Scheidegger & Spiess, 2024)
The publication “Visual Arguments” provides a window onto an imaginary archive consisting of the familiar, as well as the unknown entities of Swiss Graphic Design and Typography. This window is divided into twenty-five “visual arguments”-image clusters-each of them raising a specific topic that has not hitherto been subjected to historical inquiry. These arguments reveal aspects of design and typography practice, education, and discourse in Switzerland from the early 20th to the turn of the 21st century that go beyond the “metanarrative” of the so-called “Swiss Style.” The curated selection of images consists of graphic and typographic works, photographs, spreads from books and journals, letters, legal documents, and student work. By bringing these documents to the fore in an image-centered context rather than in a text-centered publication, Visual Arguments intends to provide an annotated collection of sources related to the history of Swiss Graphic Design and Typography. The arguments here derive from the visual source material and are formulated in short accompanying essays.